Difference in rural and urban Medicare prescription pattern for Parkinson's disease in Hawai'i. (2022) - Bruno, Michiko K.; Watanabe, Gina; Gao, Fay; Seto, Todd; Nakagawa, Kazuma; Trinacty, Connie; Brown, Stacy; Taira, Deborah A.
Abstract: Background: Medical management of Parkinson's Disease (PD) is becoming complex. Increasing evidence suggests that patients have better outcomes when they are managed by neurologists. However, access to neurologists can be limited in rural areas. Analysis of prescription pattern can provide insight into access gap rural patients face. Methods: This retrospective observational study used National Medicare Provider Utilization and Payment Data: Part D Prescriber Public Use Files from 2013 to 2018. Query was made for levodopa, dopamine agonists and other antiparkinsonian medications. The data elements obtained included drug name, number of prescribers, prescriber specialty, number of claims, number of standardized 30-day Part D prescriptions, and number of Medicare beneficiaries in the state of Hawai'i. Individual prescribing providers were categorized as urban or rural based on their cities of practice. Prescription patterns of urban and rural providers in Hawai'i as well as difference in provider specialty were compared, using standardized 30-day prescriptions as the primary measure of utilization. Results: Practice patterns differed between rural and urban areas. In rural Hawai'i, Rytary, Rotigoitne and selegiline were rarely prescribed. Levodopa percentage was higher in urban Hawai'i. In urban Hawai'i, 74.4% of the prescriptions were provided by movement disorders and general neurologists. In rural Hawai'i, 25.1% of the prescriptions were written by neurologists and 74.9% by general practitioners. Conclusions: In the state of Hawai'i, there is an urban–rural access gap to neurologists as evidenced by Medicare prescription pattern. Further study is needed to understand the reasons for rural–urban differences in prescription patterns and their impact on outcomes.